2006
DOI: 10.1038/sj.bjp.0706627
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of detrusor and corporal myocyte contraction: identifying targets for pharmacotherapy of bladder and erectile dysfunction

Abstract: The Post-Genomic age presents many new challenges and opportunities for the improved understanding, diagnosis and treatment of human disease. The long-term goal is to identify molecular correlates of disease processes, and use this information to develop novel and more effective therapeutics. A major hurdle in this regard is ensuring that the molecular targets of interest are indeed relevant to the physiology and/or pathophysiology of the processes being studied, and, moreover, to determine if they are specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 134 publications
(183 reference statements)
0
26
0
1
Order By: Relevance
“…Current theories on the pathophysiology of lower urinary tract complications of DM include dysfunction of neuropathic and myopathic components of the pelvic floor (9,10,14,23,26,33). Vaginal delivery can injure the same nerve, muscle, and connective tissues of the pelvic floor, which are responsible for maintaining continence (16,30,31,36,40).…”
Section: Discussionmentioning
confidence: 99%
“…Current theories on the pathophysiology of lower urinary tract complications of DM include dysfunction of neuropathic and myopathic components of the pelvic floor (9,10,14,23,26,33). Vaginal delivery can injure the same nerve, muscle, and connective tissues of the pelvic floor, which are responsible for maintaining continence (16,30,31,36,40).…”
Section: Discussionmentioning
confidence: 99%
“…The latter process is thought to be essential for detrusor contraction because force development is diminished in Ca 2+ channel (Ca v 1.2) knockout mice [35] or in the presence of the L-type Ca 2+ channel blocker nifedipine [22,28,38]. Thus, muscarinic receptor-induced detrusor contractions involve Ca 2+ entry via L-type Ca 2+ channels followed by uptake of Ca 2+ into intracellular stores and a subsequent release either via IP 3 -dependent or Ca 2+ -induced processes via ryanodine receptors [7,10,26].…”
Section: Introductionmentioning
confidence: 97%
“…Further support for CNP as a regulator of reproductive function comes from several studies that have shown CNP to potently stimulate cGMP production in GNRH neurons (Olcese et al 1994), pituitary gonadotrophs (McArdle et al 1993), and endocrine cells of the testis, ovaries, placenta and uterus (Khurana & Pandey 1993, Huang et al 1996, Middendorff et al 1996, Acuff et al 1997, Jankowski et al 1997, Gutkowska et al 1999, Stepan et al 2001, Walther & Stepan 2004, implicating CNP function at all levels of the hypothalamo-pituitarygonadal (HPG) axis. Furthermore, cGMP is a useful pharmacological target in the treatment of male reproductive disorders (Rosen & McKenna 2002, Christ & Hodges 2006. However, despite an ever-increasing literature detailing CNP effects in HPG tissues, understanding of the regulation and function of CNP and GC-B in neuroendocrine tissues remains poor.…”
Section: Introductionmentioning
confidence: 99%